STUDY ON SAFETY OF INSULIN ADD ON THERAPY AND ORAL HYPOGLYCEMIC AGENTS (OHGAs) IN TYPE - II DIABETES PATIENTS : STUDY ON SAFETY OF INSULIN ADD ON THERAPY AND ORAL HYPOGLYCEMIC AGENTS (OHGAs) IN TYPE - II DIABETES PATIENTS (World Journal of Current Medical and Pharmaceutical Research, 2020)
Objectives: A clinical observational investigation directed to look at the security of Insulin add-on treatment and  Hypoglycemic Agents in polypharmacy and to advance safe utilization of insulin and hypoglycemic agents in Type II Diabetes patients, through patient guiding by Clinical drug specialist at Jayabharath hospital, Nellore.Methods: A Prospective Observational investigation was directed on Type -2 Diabetes mellitus patients in the General Medicine office in a tertiary consideration emergency clinic, during the time of June – December 2019. The work was completed by utilizing quiet information assortment structures and a Diabetes survey.Results: Among 193 investigation populace with Type -2 Diabetes, hypoglycemic agents in polypharmacy 46.25% (n=108) was discovered to be more than Insulin alone, and Insulin add on treatment. Conclusion: From the examination, it was discovered that patients who are on hypoglycemic agents in polypharmacy were exposed to GI unsettling influences and who are on Insulin treatment was exposed to hypoglycemic scenes. Considering the key job of drug specialists the security of antidiabetic prescriptions and adherence was improved through patient directing.